Deconstructing a partnership: evaluating a win-win conservation and development story, the case of the Mara conservancies, Kenya - Jandreau, Connor, speaker; Hentschel, Margit, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Kenya's Maasai Mara ecosystem is a particularly contested landscape when it concerns conservation and development interests. In recent years, private conservancies have emerged, redefining the relationships between conservation, tourism and local Maasai pastoralists. The partnership forged between ecotourism operators and Maasai landowners is crowned in a community-based conservation model, bringing together a win for wildlife, and a win for livelihoods. Despite this, there are inherent trade-offs being made by various stakeholders, not least pastoralists who now have to navigate an extended network of protected area boundaries with their livestock. The conservancy is quick to point to the successes, but sufficient attention has not yet been paid to the winners and losers in the process. My research took place over the months of January to August 2013 where I explored the interface between conservation and pastoral interests. I conducted semi-structured interviews, focus groups and other qualitative research methods as a way to gauge various stakeholder positions in relation to the conservancy format. Initial findings suggest the conservancies have made strong progress in alleviating some of the historical failures inherent in East Africa's well-preserved fortress conservation story. The conservancies are beginning to fashion compatibility between tourism and livestock, where wildlife benefit. Yet the future of the conservancies remains unclear, in large part due to community concerns for livestock, resource access, and rights to self-determination. The conservancy format in Maasailand needs to consider greater efforts in fashioning a true partnership before it can consider itself a win-win enterprise.
[De]constructing a partnership: evaluating a win-win conservation and development story, the case of the Mara conservancies, Kenya
(De)constructing a partnership in the Mara conservancies, Kenya: a win-win conservation and development story?
Moderator: Margit Hentschel.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses